Challenging reintegration : a case study of halfway house, teen challenge (Singapore) - Seow, Eunice Yi Min (2016)
This study provides a deeper insight into the local halfway house scene, through an employment of the case study, Teen Challenge (Singapore). The halfway house has served as a place for offender rehabilitation, and perceived to facilitate their residents’ gradual reintegration back into society. This paper establishes that the interrelation between rehabilitation and reintegration is often fraught with contention. It should not be taken for granted. Reintegration is thus challenged, specifically on 3 levels: the Institutional, the Institutional vis-à-vis Individual, and the Individual level. A qualitative study was conducted via a series of participant observations at Teen Challenge, and semi-structured interviews with the residents. Findings gathered suggested 3 overarching themes of social displacement, disengagement, and disassociation. Critically, this paper sees these themes as interrelated, further reinforcing the offender’s lack of reintegration back into society.